Bcl‐2 maturation pattern in T‐cells distinguishes thymic neoplasm/hyperplasia, T‐lymphoblastic lymphoma, and reactive lymph nodes. Issue 3 (1st August 2017) - Ward, Nicholas; Baqai, Junaid; Zehnpfennig, Alexandra; Fine, Nancy; Huang, James; Smith, Marc D.
Abstract : Anterior mediastinal biopsies consisting predominantly of small lymphocytes can be a diagnostic challenge, especially in small core biopsies. In these cases, immunophenotyping is often employed using flow cytometry, and/or immunohistochemistry. However, due the overlap in T‐cell phenotype between thymic neoplasm/hyperplasia (THY), T‐lymphoblastic lymphoma (T‐LBL), and reactive lymph nodes (RLN), biopsies consisting predominantly of T‐cells may still be difficult to differentiate. Previous studies have shown a specific CD3/bcl‐2 staining pattern in thymic T cells of humans and mice using flow cytometry. However, the utility of this finding in distinguishing T‐cells of THY, T‐LBL, and RLN has not been carefully evaluated. Our findings show that the pattern of CD3/bcl‐2 expression in thymic T‐cells can be used to help diagnose anterior mediastinal biopsies, even when limited specimen is provided. © 2017 International Clinical Cytometry Society